Association between selenium intake and migraine: a nationwide cross-sectional study - Zhao, Leiyong; Yin, Jiahui; Li, Xiaotong; Lu, Xixue (Frontiers in Neuroscience, 2023)
Background: Dietary interventions for migraine are receiving increasing attention.However, it remains unclear whether there is any relationship between migraine and selenium intake. The aim of this study was to investigate the association between selenium intake and migraine.We used multivariate logistic regression equations to explore the association between selenium intake and migraine. Restricted cubic splines were used to examine the presence of non-linear relationships. Upon finding a non-linear relationship, a recursive algorithm was used to calculate the inflection point.Population differences were also explored through stratified analysis.Results: In the model adjusted for all covariates, the ORs (95% CI) for the association between selenium intake and migraine were 0.96 (0.88, 1.04), which was no statistical significance. However, the result of the linear trend test with quadrilles of selenium intake indicated the association between selenium intake and migraine may be non-linear. The restricted cubic splines confirmed this non-linear relationship, finding an inflection point (93.1 mcg/day), where the odds of migraine decreased with increasing selenium intake before the inflection point, and no statistically significant relationship was found after the inflection point. The association between selenium intake and migraine was non-linear in all strata except the obese.We found a non-linear association between selenium intake and migraine in the general American population.